Waste biomass-based graphene oxide decorated with ternary metal oxide (MnO-NiO-ZnO) composite for adsorption of methylene blue dye - Priyanka Barooah; Nituraj Mushahary; Bipul Das; Sanjay Basumatary (Cleaner Water)
In this study, a novel approach for the removal of methylene blue (MB) dye is effectively illustrated by using biomass based composite adsorbent. The investigation employed areca nut husk (AH) to produce graphene oxide (GO) by a single step calcination method. Thereafter, AH-GO was incorporated by using ternary metal oxide (TMO) via hydrothermal treatment. The developed AH-GO@MnO-NiO-ZnO composite was characterized by various analytical techniques, including FT-IR, XRD, FESEM, HRTEM, BET surface area and Raman spectroscopy which exhibited promising properties for dye adsorption. To study the adsorption efficiency of prepared composite, optimization experiments were performed for adsorbent dose, initial dye concentration and contact time. The optimized parameters during adsorption phenomenon were found to be 0.5 g/L of dose, 20 mg/L of initial concentration and 180 min of time exhibiting removal efficacy of 93.05 ± 0.93 %. Moreover, adsorption isotherm and kinetic models were analysed to explore the adsorption behaviour of AH-GO@MnO-NiO-ZnO towards MB dye. The adsorption isotherm and kinetic studies followed Langmuir isotherm model and pseudo-second-order (PSO) model respectively. AH-GO@MnO-NiO-ZnO has demonstrated a maximum adsorption capability of 127.06 mg/g. These findings collectively underscore the potential of AH-based adsorbent as a viable, inexpensive, and environment friendly for the treatment of wastewater contaminated with MB dye.